Estudo dos polimorfismos GSTP1 (rs1695) e TNF A-308 (rs1800629) em pacientes com COVID-19 hospitalizados e associação com dados clínicos - Vieira, Priscila da Silva Antunes (2024)
SARS-CoV-2, the new coronavirus agent of COVID-19, quickly spread throughout the world, progressing with diverse clinical manifestations, from asymptomatic, mild, moderate to severe forms, with a major outcome of death. It is still a challenge to understand the pathophysiology of SARS-CoV-2 for control measures and clinical management of the disease. Among the factors that affect the evolution of COVID-19 are: comorbidities, age, sex and lifestyle habits. Genetic factors are also the subject of investigations and may interfere with the susceptibility and evolution of the disease. The main objective of the study was to determine the allelic and genotypic frequency of GSTP1 (rs1695) and TNF A-308 (rs1800629) in patients hospitalized with COVID 19 and verify the association of polymorphisms with the severity, comorbidity, and outcome of hospitalization of patients in southern Brazil. In total, 236 patients positive for COVID-19 admitted to a reference hospital in southwestern Paraná participated in the research. A blood sample was collected from the individuals for genetic characterization using the techniques T-ARMS-PCR (tetra amplification refractory mutation system by Polymerase Chain Reaction) for rs1695 and ARMS-PCR (amplification refractory mutation system by PCR) for rs1800629. At the same time, a search was carried out in the patients' medical records to collect sociodemographic, clinical and comorbidity data. Subsequently, bivariate and multivariate analyses were conducted, including logistic regression. were Of the population, 58.1% were men and 41.9% were women; 63% were severe cases, and 37% were moderate; the hospital discharge outcome was 64%, and 36% died. The results showed that the ancestral allele was the most frequent in rs1695 (A = 71%) and rs1800629 (G = 61%) and that the genotypes AA (rs1695) and AG (rs1800629) were, respectively, 48.73% and 67.81%. For rs1695, both the A allele (OR = 2.9; 95%CI= 1.093–7.884; p=0.033) and the AG genotype (OR = 3.3; 95%CI= 1.185–9.375; p= 0.022) increase the chances of severity for COVID-19. For the rs1800629 polymorphism, no significant association was observed. Regarding hospital outcome, comorbidities, oxygen saturation and length of hospitalization, no association was observed with the investigated polymorphisms. Therefore, the study concludes that both the A allele and the AG genotype of GSTP1 rs1965 are suggestive markers of COVID-19 severity in the southern Brazilian population. And no relationship can be established for the rs1800629 polymorphism of TNF A-308.